Pengembangan Media Kartu Bergambar Berbasis Nilai Moral dalam Mengoptimalkan Kreativitas Menulis Pantun - Rahmadini, Irene; Sumardi, Aida (Arus Jurnal Pendidikan, 2024)
Grade VII students have difficulty in making pantun because they have problems in determining the initial idea for making the pantun. Pantun can be used as a medium for students to learn and improve moral values in everyday life, which now students do not apply moral values properly. In addition, learning media for learning pantun to help students find ideas for making pantun is still minimal. This is a challenge for seventh grade Indonesian language teachers in helping students find ideas for making pantun that can have a connection with moral values simultaneously. Therefore, this research aims to develop learning media in the form of picture cards that can help teachers combine the initial idea of making pantun and moral values. The development model used in this research is Research and Development using ADDIE theory. The data collection technique in this research is in the form of interviews with grade VII Indonesian language teachers and filling out questionnaires conducted by grade VII students. The results of product development research in this study have an average response from 95 students of 86% by obtaining very feasible criteria. With this percentage, the learning media that has been developed can be utilized and used in learning to write moral value-based pantun in class VII.